Incidence and causes of sudden cardiac death in athletes - Harmon, K. G. (Clinics in Sports Medicine, 2022)
Sudden cardiac death (SCD) is the leading cause of medical death in ath letes; however, many studies are significantly flawed making an accurate estimation of risk difficult. Incidence studies need to have accurate case ascertainment, a defined study population, and should be stratified by both sex and age. The risk of SCA/d in college-aged males is 1 in 35,000 person-years, black males 1 in 18,000 person-years, and higher risk sports include men`s basketball, men`s soccer, and American football. Inherited cardiomyopathies and electrical conditions account for w 2/3 of off SCA/d and can be detected with an ECG. More research is needed to provide more granular estimates.